# alg2 check?

solve 3(8x-2)=46-2(12x+1)

24x-6=46-24x+2
24x-6=48-24x
48x-6=48
48x=42
x=42/48 or 7/8
what where the two mistakes made in the problem?

I said the 46 going to 48 and subtracting the 6 from 48?

1. correct solution:

24x-6=46-24x-2
48x = 50
x = 50/48 = 25/24

the first major error is the +2 instead of -2
second error is subtracting 6 instead of adding 6 to both sides

I think you had picked them out correctly

posted by Reiny

## Similar Questions

1. ### algebra

Did I do this problem the correct way if so is there a shorter way to explain this? x(x + 6)(x + -4) = 24x x(6 + x)(x + -4) = 24x x(6 + x)(-4 + x) = 24x (6 + x) * (-4 + x x(6(-4 + x) + x(-4 + x)) = 24x x((-4 * 6 + x * 6) + x(-4 +
2. ### algebra

24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
3. ### calculus

i need to find the derivative using chain rule: (x^2 + 2x - 6)^2 (1-x^3)^2 i got the answer from a site but the problem is i cannot get my work to match up with the answer, i don't know what im doing wrong. answer: 10x^9 + 36x^8
4. ### Algebra (Re.: Reiny)

The fact that there was that nice symmetry to the question, makes it easier than it first appears. I had it as: (a/b + b/a)รท(b/a - a/b) look at (a/b + b/a) the common denominator for this would be ab, so a/b + b/a = (a^2 +
5. ### algebra

24x^4-12x^3+48x^2/-4x=6x^3-3x^2-4x
6. ### Math

consider the equations:f(x)=-6x-1 and g(x)=4x^2 Select the solution for (f+g)(x) A) -6x-1+4x^2 B) -24x^3 - 4X^2 C) -24x^2 - 1 D) -6X -1 - 24X^2 I think the answer is A. Please help
7. ### Maths

is this correct... (3x^2+4x-3)^2-(3x^2-x+2)^2 then is it this (9x^4+24x^3-2x^2-24x+9)-(9x^4-6x^3+13x^2-4x+4) or this 9x^4+24x^3-2x^2-24x+9-9x^4-6x^3+13x^2-4x+4 should it have brakets or not that's my only problem thanks
8. ### alg

Which of the following is equivalent to the rational number [3x / 4x]? a) 6x / 8x b) 12x / 24x c) 48x / 56x d) 3x / 5x a
9. ### math help

5) Consider the equations: f(X)= -6x-1 and g(x)=4x^2 Select the solution for (f+g)(x). a) -6x -1 + 4x^2 b) -24x^3 - 4x^2 c) -24x^2 - 1 d) -6x - 1- 24x^2
10. ### Algebra 1

Rewrite the polynomial in descending order in its simplest form. here is #1 12x^2 y^2 z^3+2+24x^2 I think it should be writen 12x^2y^2Z^3+24x^2+2 then there is also question #6 I need help with is it x+y+xy+3x+4x^2 I think it

More Similar Questions